(untitled) (Fiep Bulletin - online, 2011)
Descriptive, exploratory and representational study, with a qualitative approach, aimed to seize, from graphics resources, the discursive practices of non-conceptual representational field of Mental Health in story and thematic drawing and the Theory of Social Representations. 30 students participated, that craft, individually, a mask at its discretion, regardless of style or theme. It was identified six thematic fields: Thematic Field 1 – Projective Mechanism and Indifference; Thematic Field 2. Identity construction and Idealization; Thematic Field 3. Narcissism interests interplay: indecision and expectations; Thematic Field 4. Dreaming, dancing, bringing joy and releasing; Thematic Field 5. Truths regulated by Social Frame; Thematic Field 6. Difficulties to decide, to construct and to talk about itself. On one hand, it appears that the mental and behavioural disorders, to the investigated psychosocial subjects, is a content away from them, although it’s part of their teaching-learning process. On the other, it was an instrumental strategy in favors of knowing reality and action.